A review of approaches to improve participation of culturally and linguistically diverse populations in clinical trials. Issue 1 (December 2016) - Hughson, Jo-anne; Woodward-Kron, Robyn; Parker, Anna; Hajek, John; Bresin, Agnese; Knoch, Ute; Phan, Tuong; Story, David
Abstract The under-representation of culturally and linguistically diverse participants in clinical trials is an ongoing concern for medical researchers and the community. The aim of this review is to examine the complex issue of recruiting culturally and linguistically diverse (CALD) older people to medical research and to examine responses to these issues. The review focuses on (1) trends in the existing literature on barriers to and strategies for recruiting CALD and older people to clinical research, (2) issues with informed consent for CALD populations, and (3) the efficacy of innovative approaches, including approaches incorporating multimedia in research and consent processes. The literature indicates that predominant barriers to greater involvement of CALD patients in clinical trials are communication, including literacy and health literacy considerations; English language competence; and cultural factors in the research setting such as mistrust of consent processes, as well as considerable practical and logistical barriers, including mobility considerations. Some evidence exists that incorporating multimedia resources into the informed consent process can improve patient understanding and is preferred by patients, yet these findings are inconclusive. A multi-methodological approach, including the use of culturally and linguistically sensitive multimedia tools, may help address the issue of low inclusion of CALD groups in clinical research. Researcher education needs to be taken into account to address preconceptions about CALD resistance to research participation and to raise awareness of cultural concerns in regard to research participation.